Alterations to the Gut Microbiota and Their Correlation With Inflammatory Factors in Chronic Kidney Disease - Li, FengXia; Wang, MeiHong; Wang, JunPing; Li, RongShan; Zhang, YaQiong (Frontiers in Cellular and Infection Microbiology, 2019)
Alterations to the gut microbiota have been previously suggested to be tightly linked to chronic systemic inflammation, which is a major contributing factor to complications and disease progression in chronic kidney disease (CKD). Nevertheless, the effect of gut dysbiosis on the pathogenesis and/or production of inflammatory factors in CKD has not been extensively studied to date. In the present study, we conducted 16S ribosomal DNA pyrosequencing using fecal microbiota samples and analyzed the production of serum inflammatory factors in 50 patients with CKD and 22 healthy control (HC) subjects. The results revealed that compared to the HC subjects, patients with CKD exhibited a significant reduction in the richness and structure of their fecal microbiota. At the phylum level, compared to the HC group, patients with CKD also presented reduced abundance of Actinobacteria but increased abundance of Verrucomicrobia. Moreover, the genera Lactobacillus, Clostridium IV, Paraprevotella, Clostridium sensu stricto, Desulfovibrio, and Alloprevotella were enriched in the fecal samples of patients with CKD, while Akkermansia and Parasutterella were enriched in those of the HC subjects. Finally, we analyzed whether these changes to the fecal microbiota correlated with CKD clinical characteristics and/or the production of known inflammatory factors. Altered levels of the microbiota genera Parasutterella, Lactobacillus, Paraprevotella, Clostridium sensu stricto, and Desulfovibrio were shown to be correlated with CKD disease-severity indicators, including the estimated glomerular filtration rate. Most notably, Akkermansia was significantly negatively correlated with the production of interleukin-10. The results of the present study suggest that microbiota dysbiosis may promote chronic systemic inflammation in CKD. Furthermore, they support that modifying the gut microbiota may be a promising potential therapeutic strategy to attenuate the progression of, and/or systemic inflammation in, CKD.